1992
DOI: 10.1103/physrevb.45.11749
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the optical dielectric function of semiconductors: Extension of the critical-point parabolic-band approximation

Abstract: A model is proposed for the line shape of the optical dielectric function of zinc-blende semiconductors. For comparison with previously proposed models, this model is used primarily with spectroscopic ellipsometry data (but also transmission data below 1.5 eV) to obtain an analytic room-temperature dielectric function for GaAs. It is found to be more generally valid than the harmonic-oscillator model, the critical-point (CP) model, or the model of Adachi. It is applicable over the entire range of photon energi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
189
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 324 publications
(193 citation statements)
references
References 41 publications
4
189
0
Order By: Relevance
“…The inclusion of an additional term, 1ϱ , in the ͑E͒ expression improves the fit of experimental data. [11][12][13][14][15][16] This term contains the contributions of higher lying interband transitions. The 1ϱ parameter may take a second order polynomial dependence of the photon energy 16 or may even be constant [11][12][13][14][15] in the studied spectral range.…”
Section: Theoretical Modelmentioning
confidence: 99%
“…The inclusion of an additional term, 1ϱ , in the ͑E͒ expression improves the fit of experimental data. [11][12][13][14][15][16] This term contains the contributions of higher lying interband transitions. The 1ϱ parameter may take a second order polynomial dependence of the photon energy 16 or may even be constant [11][12][13][14][15] in the studied spectral range.…”
Section: Theoretical Modelmentioning
confidence: 99%
“…Kim and Garland have developed a KK consistent model that adequately describes the semiconductor dielectric function above, below, and through the fundamental direct gap. 50,51 It can accurately describe the dielectric function and higher order derivatives. However, to determine the required internal parameters a two stage fitting process is needed.…”
Section: Optical Modelingmentioning
confidence: 99%
“…The fact that Lorentzian broadening does not describe the optical spectrum accurately has already been recognized and discussed by several groups. [20][21][22][23] Rakić and Majewski 23 have shown that the Adachi model, with a Gaussian-like broadening function, can describe accurately the dispersion and absorption of GaAs and AlAs even in the vicinity of the E 0 , where the original model of Ozaki and Adachi 9 is highly inaccurate. In this work, we use a similar model, which considers the contribution of exitonic terms only at E 0 , E 0 ϩ⌬ 0 CPs, since the excitonic effects are usually more pronounced at E 0 than at any other CPs.…”
Section: Introductionmentioning
confidence: 99%